Güçlendirilmiş dental seramiklerin vickers sertlikleri ve yük altında kırılma davranışları - Celal Artunc; Bulent Gokce; Mutlu Ozcan; Mine Dundar; M Ali Gungor; M Erhan Çömlekoglu (Cumhuriyet University, 2011)
Objective: The objectives of this study were to determine the Vicker`s hardness of reinforced dental ceramics and determine the modes of fractures under load. Methods: Four ceramic core groups (n=7/group) from leucite (Evopress,Wegold&De), low leucite (Finesse, Ceramco), glass-infiltrated (Inceram Alumina,Vita) and lithium disilicate materials (E.max press, Ivoclar) were fabricated according to each manufacturers' instructions (thickness: 3 mm, diameter: 5 mm). Their individual veneering ceramics were vibrated, condensed in a stainless steel mold (diameter: 5 mm, height: 5 mm) and fired on the core materials. The specimens were stored in distilled water at 37°C for 24 hours prior to indentation tests and embedded in polyesther moulds. Vickers hardness values (DUH±SD) were measured (cross-head speed:7,2 gf/s, load:200 gf) and statistically analysed (ANOVA). A load of 400 N was applied on the surfaces of specimens with a diamond indentor (diameter:1 mm) at the macro hardness test machine for crack formation. The crack modes for each group were observed under the scanning electrone microscope. Results: The Vickers hardness values for low leucite veneering ceramic were significantly (P<0.05) higher (236±17), followed by the leucite (129±51), glass-infiltrated (117±38), and lithium disilicate (85±34) veneering ceramic materials in decreasing order. Mainly radial or cone cracks were observed after the application of load. Conclusion: The increase in the hardness of the material led to more crack formation and resulted in longer cracks. No crack formation extending to the core materials were observed in neither of the ceramic groups under these experimental conditions. ÖZET Amaç: Bu çalışmanın amacı güçlendirilmiş dental seramiklerin Vickers sertlik değerlerinin ve yük altındaki kırılma şekillerinin belirlenmesidir. Gereç ve Yöntem: Lösit (Evopress,Wegold&De), düşük lösit (Finesse, Ceramco), cam infiltrasyonlu aluminöz seramik (Inceram Alumina,Vita) ve lityum disilikat (E.max press, Ivoclar) bazlı dört farklı seramik alt yap_ materyali (n=7/grup) her bir üretici firmanın önerileri doğrultusunda hazırlandı (3 mm kalınlıkta; 5 mm çapta). Her bir alt yapı seramiğine özgü kaplama seramikleri; paslanmaz çelik bir metal kalıpta (5mm çap 5mm yükseklikte) vibrasyonla kondanse edildi ve alt yapı seramiklerinin üzerine pişirildi. Örnekler batırma testlerinden önce 37°C' de 24 saat distile suda bekletildikten sonra polyester kalıplara gömüldü. Vickers sertlik değerleri (DUH±SD) ölçüldü (çene hızı:7,2 gf/s, yük:200 gf) ve veriler istatistiksel olarak analiz edildi (ANOVA). Çatlak oluşumu için örneklerin üst yüzeylerine makro sertlik test cihazında batıcı elmas uç ile (1 mm çaplı) 400 N yük uygulandı. Alınan taramalı elektron mikroskop görüntüleri ile her bir gruba ilişkin çatlak şekilleri gözlemlendi. Bulgular: Gruplar arasında ortalama Vickers sertlik değerleri düşük lösit grubu için anlamlı olarak (P<0.05) en yüksek bulunur iken (236±17), bunu lösit (129±51), cam infiltrasyonlu aluminöz seramik (117±38), ve lityum disilikat (85±34) kaplama seramik materyalleri azalan sırayla izledi. Yük uygulaması sonrasında genellikle ışınsal ya da koni şekilli çatlakların oluştuğu gözlendi. Sonuç: Seramik materyalin sertliğinin artması daha fazla ve daha uzun çatlak oluşumuna yol açtı. Bu çalışmadaki deneysel koşullar altında kaplama seramik gruplarının hiçbirinde alt yapı seramiklerine ulaşan çatlak oluşumu gözlenmedi.